Novel Immunotherapies for Autoimmune Hepatitis - Cassim, Shamir; Bilodeau, Marc; Vincent, Catherine; Lapierre, Pascal (Frontiers in Pediatrics, 2017)
Autoimmune hepatitis (AIH) is a multifactorial autoimmune disease of unknown pathogenesis, characterized by a loss of immunological tolerance against liver autoantigens resulting in the progressive destruction of the hepatic parenchyma. Current treatments are based on non-specific immunosuppressive drugs. Although tremendous progress has been made using specific biological agents in other inflammatory diseases, progress has been slow to come for autoimmune hepatitis patients. While current treatments are successful in the majority of patients, treatment discontinuation is difficult to achieve and relapses are frequent. Lifelong immunosuppression is not without risks, especially in the pediatric population; 4% of patient with type 1 AIH will eventually develop hepatocellular carcinoma with a 2.9% probability after 10 years of treatment. Therefore, future treatments should aim to restore tolerance to hepatic autoantigens and induce long-term remission. Promising new immunotherapies have been tested in experimental models of autoimmune hepatitis including T and B cell depletion and regulatory CD4+ T cells infusion. Clinical studies on limited numbers of patients have also shown encouraging results using B-cell depleting (Rituximab) and anti-TNF-alpha (Infliximab) antibodies. A better understanding of key molecular targets in AIH combined with effective site-specific immunotherapies could lead to long-term remission without blanket immunosuppression and with minimal deleterious side effects.